Shakespearean cultures: Latin America and the challenges of mimesis in non-hegemonic circumstances - Rocha, João Cezar de Castro (Studies in violence, mimesis, and culture, 2019)
"Shakespearean Cultures proposes a new theoretical framework that, based upon the concepts of "poetics of emulation" and "deauratized art," offers a groundbreaking approach to the understanding of the asymmetries of the world-system, triggered by the emergence of the modern world"--